Visual, auditory, and kinesthetic learning model on the mathematics problem solving ability - Ikawati, Oktavia Nadia; Kowiyah, Kowiyah (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aimed to determining the effect of using VAK (Visual, Auditory and Kinesthetic) learning model on the mathematics problem solving abilities. This study utilized a quantitative method with a research design Post-Test Only Control Design. The instrument is used a test of mathematics problem solving abilities that has been validated by expert lecturers. Accordingly, the data has reliable instrument. The data in the Requirements Test analysis encompassed the normality and homogeneity tests. Hence, the variance data of the group an homogeneous distribution. Besides in the Hypothesis Test utilizing the t-test, it was attained that t count = 3.544 > ttable = 2.001. Accordingly, from the data of the two classes, H1 is accepted. Hence, There is a significant effect between the VAK (Visual, Auditory and Kinesthetic) learning model and the class that does not utilize it.